DEVELOPMENT OF AN ANDROID-BASED TRAFFIC LIGHT SYSTEM APPLICATION - HENDRIYANI, TRI HENDRIYANI (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2025)
Traffic light systems play a crucial role in regulating vehicle flow at road intersections. However, most existing systems still rely on fixed-time settings, with adjustments for normal conditions and flashing yellow lights controlled conventionally through hardware based on traffic conditions. This study aims to design and develop a traffic light system that can be operated and accessed via an Android application using Wi-Fi connectivity. The system allows for flexible adjustments of traffic light conditions by operators, facilitating traffic management and enabling use in specific situations such as for emergency vehicles and VVIP vehicles. The system supports various traffic light modes, such as all red lights (All Red), flashing yellow lights (Flashing Kuning), a manual mode for controlling individual lights, and a normal mode with an automatic timing cycle similar to conventional systems. The system is designed using an ESP32 microcontroller as the main controller and an Android application as the user interface. The implementation involves communication between hardware and software over a Wi-Fi network. Testing results indicate that the system functions effectively, with quick responses to commands sent through the application, and can operate at a distance of 10"“50 meters. This development is expected to provide a more flexible solution for traffic management, both for simulation purposes and real-world implementation.